Evaluation Study of English Textbook for Indonesian Junior High Schools - Nurul Lailatul Khusniyah (Universitas Islam Negeri (UIN) Mataram, 2019)
The aim of this study is to get the quality of the English textbook for Junior High School that was designed by the government. Is it appropriate with the students and context needs? Method of research is the evaluation method through content analysis. Model of evaluation is Discrepancy Evaluation Model (DEM) to know suitability or unsuitability of textbook using criteria of evaluation. The instrument of assessment has 8 criteria, namely goals, approach, language content, skills, topics, methodology, teacher’s book, and practical consideration. Validation of instrument is judgment expert. The result of research found that the English textbook “Bahasa Inggris Think Globally Act Locally Class IX” has a good quality. It can be seen from the percentage of criteria, such as goals 80.8%, approach 82,8%, language content 81%, skills 81,3%, topics 87%, methodology 78.8%, teacher’s book 56.8%, and practical consideration 82.3%.